Regulation of PI3K by PKC and MARCKS: Single-Molecule Analysis of a Reconstituted Signaling Pathway - Brian P. Ziemba; John E. Burke; Glenn R. Masson; Roger Williams; Joseph J. Falke (2016)
In chemotaxing ameboid cells, a complex leading-edge signaling circuit forms on the cytoplasmic leaflet of the plasma membrane and directs both actin and membrane remodeling to propel the leading edge up an attractant gradient. This leading-edge circuit includes a putative amplification module in which Ca(2+)-protein kinase C (Ca(2+)-PKC) is hypothesized to phosphorylate myristoylated alanine-rich C kinase substrate (MARCKS) and release phosphatidylinositol-4,5-bisphosphate (PIP2), thereby stimulating production of the signaling lipid phosphatidylinositol-3,4,5-trisphosphate (PIP3) by the lipid kinase phosphoinositide-3-kinase (PI3K). We investigated this hypothesized Ca(2+)-PKC-MARCKS-PIP2-PI3K-PIP3 amplification module and tested its key predictions using single-molecule fluorescence to measure the surface densities and activities of its protein components. Our findings demonstrate that together Ca(2+)-PKC and the PIP2-binding peptide of MARCKS modulate the level of free PIP2, which serves as both a docking target and substrate lipid for PI3K. In the off state of the amplification module, the MARCKS peptide sequesters PIP2 and thereby inhibits PI3K binding to the membrane. In the on state, Ca(2+)-PKC phosphorylation of the MARCKS peptide reverses the PIP2 sequestration, thereby releasing multiple PIP2 molecules that recruit multiple active PI3K molecules to the membrane surface. These findings 1) show that the Ca(2+)-PKC-MARCKS-PIP2-PI3K-PIP3 system functions as an activation module in vitro, 2) reveal the molecular mechanism of activation, 3) are consistent with available in vivo data, and 4) yield additional predictions that are testable in live cells. More broadly, the Ca(2+)-PKC-stimulated release of free PIP2 may well regulate the membrane association of other PIP2-binding proteins, and the findings illustrate the power of single-molecule analysis to elucidate key dynamic and mechanistic features of multiprotein signaling pathways on membrane surfaces.